Tarenna flava Alston (Rubiaceae): A New Record for Kerala from Agasthyamalai Biosphere Reserve, Western Ghats, India - Murugan, Perumal; Sulaiman, Mohammed; Paul, Basil (Indian Forester, 2020)
No Abstract.